2011
DOI: 10.1111/j.1467-8667.2011.00741.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Tension Stiffening Behavior in FRP‐Strengthened RC Members Based on Rigid Body Spring Networks

Abstract: Allowing for the tension stiffening effects resulting from the bond between steel reinforcement and surrounding concrete leads to effective deformation analysis of reinforced concrete (RC) members when using a nonlinear finite element analysis modeled on the smeared crack concept. Nowadays, externally bonded fiber reinforced polymer (FRP) composites are widely used for strengthening existing RC structures. However, it remains unclear to what extent the tension stiffening of postcracking concrete is quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 39 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…When comparing the calculated and measured values for the CFRP strain, it can be noticed that there is a good match at the start. But on the verge of the failure, there is a bigger difference between the calculation and the measurement, because there is higher tension stiffening (see also Dai et al, 2012). The measured value is about 10% lower than the calculated one.…”
Section: Influence Of the Curvaturementioning
confidence: 99%
“…When comparing the calculated and measured values for the CFRP strain, it can be noticed that there is a good match at the start. But on the verge of the failure, there is a bigger difference between the calculation and the measurement, because there is higher tension stiffening (see also Dai et al, 2012). The measured value is about 10% lower than the calculated one.…”
Section: Influence Of the Curvaturementioning
confidence: 99%
“…Extensive experimental, analytical and numerical studies have shown the effectiveness of this technique in improving the strength and stiffness of RC elements. Although the effect of FRP application and FRP-concrete bond on the ultimate limit state (ULS) behavior of strengthened elements have been extensively studied [1,2], their effect on the service limit state (SLS) behavior and cracking has received less attention [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The available results show FRP application affects the stiffness and deformation of the strengthened elements and leads to reduction of crack spacing and width [5,8]. The analytical and numerical investigations on this subject are also still limited [3,7,9,10] and comprehensive models describing the tension stiffening with detailed consideration of micromechanical mechanisms are scarce. As for macro-modeling, suitable constitutive models, as the main inputs of smeared crack modeling approaches, are not available yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sutton (Ke et al., ; Reu et al., ; Sutton et al., , ) started to study image correlation techniques for photogrammetry in the early 1980s until now, with several publications in two‐ and three‐dimensional Digital Image Correlation (DIC; Sutton et al., ). Since then photogrammetry has been increasingly used as an additional tool in various engineering tests such as load tests, monitoring structures, crack measurements (Dai et al., ; Huang et al., ; Iyer and Sinha, ; Nishikawa et al., ; Park et al., , ).…”
Section: Introductionmentioning
confidence: 99%